AN ASSESSMENT OF PROFESSIONALS’ PERCEPTION OF THE SUSTAINABILITY PERFORMANCE OF INFRASTRUCTURE PROJECTS IN NIGERIA - Amadosi-Jesse EMMANUEL; Ahmed Doko IBRAHIM; Kulomri Jipato ADOGBO (Journal of Construction Project Management and Innovation)
Construction activities lead to the provision of infrastructure. However, these activities have undesirable impact on t he environment. Various management approaches have evolved to guide construction participants in achieving better sustainability performance of infrastructure project. However, methods for evaluating the sustainability performance of infrastructure project s across economic, social and environmental aspects are not covered in literature. This paper aimed to assess professionals’ perception of sustainability performance of infrastructure projects in Nigeria. The research adopted a questionnaire survey of prof essionals in the Nigerian Construction industry. 100 questionnaires were distributed and a total of 72 valid responses were obtained and used in the analysis. The research found that sustainability performance of infrastructure projects in Nigeria fall bet ween moderate performances to high performance. Some factors whose performance falls below a set standard and adversely affect sustainability performance include ozone protection, modular and standardised design, discharge of water. The study recommends t hat government policies which incorporate the assessment of proposed infrastructure across social, economic and environmental impacts should be formulated to improve sustainability performance of infrastructure projects.